Multicystic Renal Cell Carcinoma: A Rare kidney Tumor in Children - Atilgan, Dogan; Uluocak, Nihat; Erdemir, Fikret; Parlaktas, Bekir Suha; Koseoglu, Resit Dogan; Boztepe, Ozgur (Urology Journal, 2013)